2010
DOI: 10.1080/13803395.2010.493144
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific contribution of the human striatum to perceptual–motor skill learning

Abstract: Acquisition of new perceptual-motor skills depends on multiple brain areas, including the striatum. However, the specific contribution of each structure to this type of learning is still poorly understood. Focusing on the striatum, we proposed (a) to replicate the finding of impaired rotary pursuit (RP) and preserved mirror tracing (MT) in Huntington's disease (HD); and (b) to further explore this putative learning dissociation with other human models of striatal dysfunction (i.e., Parkinson's disease and foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The putamen activation at Recall, but not during Learning, echoes prior reports that basal ganglia dysfunction due to Parkinson’s or Huntington’s disease does not affect sensory-motor adaptation while impairing recall (Bédard and Sanes 2011; Marinelli et al 2009; Smith and Shadmehr 2005; see also Cavaco et al 2010) and transfer of learning from the right to the left limb (Isaias et al, 2010). Thus, basal ganglia circuits may not have substantial involvement in forming new sensory-motor memory, but these circuits may participate more in their rehearsal and automatization.…”
Section: Discussionsupporting
confidence: 79%
“…The putamen activation at Recall, but not during Learning, echoes prior reports that basal ganglia dysfunction due to Parkinson’s or Huntington’s disease does not affect sensory-motor adaptation while impairing recall (Bédard and Sanes 2011; Marinelli et al 2009; Smith and Shadmehr 2005; see also Cavaco et al 2010) and transfer of learning from the right to the left limb (Isaias et al, 2010). Thus, basal ganglia circuits may not have substantial involvement in forming new sensory-motor memory, but these circuits may participate more in their rehearsal and automatization.…”
Section: Discussionsupporting
confidence: 79%
“…This pattern of intact learning combined with poor retention of gains after two years is similar to a pattern observed on classic perceptual-motor skill learning tasks in samples selected according to similar criteria (Kennedy and Raz 2005; Rodrigue et al 2005), and is in accord with commonly reported age deficits in acquisition (Wright and Payne 1985; Smith et al 2005; Seidler 2006; Janacsek et al 2012; Coats et al 2013) and retention of the task-relevant skills after long delays (Fisk et al 1994). Deficits indexed by navigation distance were conjointly explained by smaller volume and greater iron content of the caudate nuclei, as well as smaller volume of cerebellar hemispheres—regions commonly implicated in perceptual-motor skill acquisition and maintenance (e.g., Raz et al 2000; Ungerleider et al 2002; Cavaco et al 2011) as well as spatial navigation (Rondi-Reig and Burguiere 2005; Moffat 2009). This is partly consistent with our previous cross-sectional report of correlation between navigation time and Cb volume (Daugherty et al 2015a), although in that study, Cd volume was unrelated to navigation efficiency.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Within traditional motor adaptation paradigms, adaptive learning is assessed by the degree of the after-effect observed during a de-adaptation task and the amount of savings upon a second exposure to the adaptation task (i.e., a readaptation task). In context of the present study, locomotor adaptation is a process during which changes in locomotor output are stabilized over time by the central nervous system's incorporation of feed-forward predictive motor actions and sensorimotor feedback [13][14][15][16][17][18][19]. While locomotor adaptation has previously been induced within the laboratory setting using a variety of different methods, Hoffland et al utilize a locomotor adaptation paradigm using a split-belt treadmill.…”
mentioning
confidence: 99%